Detection of Volatile Organic Compounds Using Langmuir-Blodgett Films of Zinc-Porphyrin and Zinc-Phthalocyanine. Issue 5 (3rd May 2016) - Yang, Wenyao; Xu, Jianhua; Mao, Yunwu; Yang, Yajie; Jiang, Yadong
Abstract : Detection of volatile organic compounds (VOCs) by electronic optical nose based on sensing thin films is becoming more interesting in modern industry and daily life. The thin films of zinc-porphyrin and zinc-phthalocyanine fabricated by Langmuir-Blodgett (LB) technique onto quartz substrates have been used as sensing elements for electronic optical nose application. Absorption spectra range of the both organic elements in a chloroform solution and the LB solid state thin films were acquired by using a UV-1700 spectrometer. As an electronic gas sensing test, the optical absorbance performance after the exposure of LB films to different VOCs, and dry air was investigated. The results indicated that the ZnTPP and ZnPc LB films showed different gas sensitivity due to different molecule structure. Besides, a 2 × 1 colorimetric array is fabricated by immobilizing sensing thin film on a silica substrate, and the vapor molecules of pyridine and methanol can be easily detected.